A Branch of Magic, or the Possibility of Myth in Esther Kinsky’s Am Fluß - Ben Pestell (Studies in 20th & 21st Century Literature, 2020)
This article demonstrates how literary walks can evoke myth in a meaningful way for contemporary life. In particular, through a close reading of Esther Kinsky’s Am Fluß [River], I argue that the landscape experienced on foot can articulate and give access to the transcendent component of myth. I begin with a survey of how magic and transcendent experience is configured in related literary forms (namely new nature writing, the post-secular, new materialism, and the literature of re-enchantment) but remains bound by material reality. I then define the meaning and function of myth in relation to contemporary literature. These general observations lay the ground for a reading of Kinsky’s novel which focuses on the mythical symbolism of the protagonist’s solitary walks in the edgelands around London’s River Lea (among other locations). Although Am Fluß ostensibly resists both categories of “myth” and “psychogeography,” it walks the city, symbolically using myth in a way which works against dominant (nationalist and capitalist) structures of power. I finally consider the relationship between the novel and the potential for the purifying or expiatory powers of walking and walking literature. Like myth, Am Fluß brings an ineffable situation within the bounds of thought and comprehension, exemplifying a productive relationship with the environment.
Keywords: literary walks; myth; Esther Kinsky; re-enchantment; psychogeography; London